The Role of The IRE Teacher in Shaping The Attitude of Student's Religious Moderation - Rusdi Anshori Harahap; Zaini Dahlan; Usiono Usiono (Nazhruna: Jurnal Pendidikan Islam, 2022)
The diversity of society is the wealth of the Indonesian nation, as well as efforts to moderate this diversity as a form of practicing the values ​​of the precepts of Indonesian unity, including informal education (schools/madrasah). This article aims to describe the role of IRE (Islamic Religious Education) teachers in shaping students' attitudes toward religious moderation at SMK Swasta Teladan 1 North Sumatra. This study uses a qualitative approach with a descriptive study method. The research data were obtained using observation, interview, and document studies. Furthermore, data analysis uses reduction techniques (information/data sorting), data presentation, and drawing conclusions. Finally, the research data was declared valid after the triangulation technique test. The results of this study indicate that teachers (educators) act as conservators, innovators, transformers, and organizers in shaping students' religious moderation attitudes in schools. Through this research, it is hoped that it can add to the scientific treasures and become the concept of building religious moderation in schools.